A matter of love and labour? Parents working as personal assistants for their adult disabled children. Issue 1 (2nd January 2016) - Olin, Elisabeth; Dunér, Anna
Abstract : The overall aim was to explore experiences of parents working as personal assistants (PAs) for their adult disabled children, with a focus on the roles of these parents and the intersection between formal and informal support. In 1994, the right to personal assistance was introduced in Sweden. The intention was to promote disabled people's independence and participation in society. Many users combine personal assistance from family members with non-family assistance. Employing parents of adult children as PAs has been depicted as a barrier to independence and adulthood, but can also be seen as lessening potential difficulties of having 'strangers' deliver support in the private sphere. Welfare policies and social work practices have a major impact on the lives of families with disabled children. Fourteen parents working as PAs for their adult children were interviewed. For the parents, pursuing an employee role outside the home was very difficult to combine with the caring role. Shortcomings in the formal support system and battles with social services to receive adequate and appropriate support were experienced as burdensome. Families with disabled members were forced into very traditional family patterns and found themselves interwoven into a complex fabric of emotional and economic interdependence.